2009
DOI: 10.1007/s00774-009-0118-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dietary intake, education, and physical activity on bone mineral density among North Indian women

Abstract: The aim of the study was to determine the relationship of dietary nutrients and bone mineral density (BMD) in North Indian women. This cross-sectional study was conducted from April 2006 to March 2008. Subjects included 255 healthy women, aged 20-69 years, who were relatives of patients being admitted in the hospital. Various demographic characteristics including socioeconomic status and serum parameters in relationship to BMD were evaluated. In addition, the daily dietary intake of energy, protein, fat, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 25 publications
5
37
0
Order By: Relevance
“…The only correlation we observed, that between cottage cheese consumption and BMI, could have been attributed to the general observation that individuals with lower BMI consume more cottage cheese, also confirmed by other researchers (43) . In the present group of females, correlations were observed between Ca intake from various dairy sources and BMD that corresponded to the results of other authors, claiming similar correlations between Ca intake and BMD (39,44,45) . In contrast, the observed negative correlation between Ca intake from dairy dishes and total hip BMD score is rather difficult to explain.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The only correlation we observed, that between cottage cheese consumption and BMI, could have been attributed to the general observation that individuals with lower BMI consume more cottage cheese, also confirmed by other researchers (43) . In the present group of females, correlations were observed between Ca intake from various dairy sources and BMD that corresponded to the results of other authors, claiming similar correlations between Ca intake and BMD (39,44,45) . In contrast, the observed negative correlation between Ca intake from dairy dishes and total hip BMD score is rather difficult to explain.…”
Section: Discussionsupporting
confidence: 92%
“…According to other authors, the daily Ca intake of postmenopausal women is significantly lower than that of premenopausal women (39) and the proportion of women with low Ca intake rises with age (26,37) . However, the character of the relationship is not obvious, as other authors report lower Ca inadequacy in women above 75 years of age (36) , probably associated with higher intake of Ca supplements (14) .…”
Section: Discussionmentioning
confidence: 95%
“…Regarding the relationship between vitamin B1 intake and bone growth, no report has been found. However, there are some reports (29,30) that show a positive association between energy intake and bone mass, though energy intake was excluded from the independent variables to avoid collinearity in our study. Vitamin B1 acts as a cofactor for the metabolism of carbohydrates, helping to turn starch and sugar into the energy our bodies need.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have identified age, sex, body weight, body mass index (BMI), living habits, dietary factors (including calcium, vitamin D, caffeine and alcohol etc. ), physical activity levels, and genetic variations might influence the individual BMD status (Kumar et al, 2010, Waugh et al, 2009, Karasik et al, 2016, Nguyen et al, 2000). Intervention strategies that have been developed based on these findings may increase the BMD and subsequently reduce osteoporosis or risks of fragility fractures have been widely recommended by clinical physicians.…”
Section: Introductionmentioning
confidence: 99%